Variability in tumor margin reporting for soft tissue sarcoma and cutaneous mast cell tumors in dogs: A systematic review. Issue 2 (16th December 2020) - Abrams, Brittany E.; Putterman, Allison B.; Ruple, Audrey; Wavreille, Vincent; Selmic, Laura E.
Abstract: Objective: To identify which classification systems have been used for tumor margin reporting and to determine whether factors (publication year, tumor type, and specialty of the contributing authors) influenced trends in margin reporting within literature describing canine soft tissue sarcoma (STS) and cutaneous mast cell tumors (MCT). Study design: Systematic literature review. Methods: Eligible articles were identified through electronic database searches performed for STS and MCT. Data abstracted from relevant studies included publication year, author list, specialty of contributing authors, criteria used to report the planned surgical margins, and the status of histologic margins. Categorization of papers was based on the classification systems used to report surgical and histologic tumor margins. Results: Fifty‐three articles were included, 11 on STS, 37 on MCT, and five that included both tumor types. Criteria for classifying the planned surgical margins were described in only 50.9% of studies. Articles that listed a veterinary surgeon as a contributing author ( P = .01) and STS articles compared to MCT papers ( P = .01) were more likely to report surgical margins. Most (56.6%) studies reported the status of histologic margins dichotomously as "complete" or "incomplete." Although a previously published consensus statement recommended that quantitative criteria be used to report histologic margins, only 7.5% of articles used quantitative methods. Conclusion: Classification systems used for reporting tumor margins were highly variable among studies. Clinical significance: The findings of this review provide evidence that a standardized classification system for reporting surgical and histologic tumor margins is required in veterinary medicine. A universal system may support more consistent reporting of neoplastic biopsy specimens and allow for more meaningful comparisons across research studies.